Grain boundary properties of a nickel-based superalloy: characterisation and modelling - Alabort, E; Barba, D; Sulzer, S; Lißner, M; Petrinic, N; Reed, RC (Elsevier, 2018)
Miniaturised tensile tests coupled with in-situ scanning electron microscopy are used to deduce the grain boundary properties of a nickel-based superalloy at 750 °C. This allows the damage initiation, evolution and failure processes to be observed directly. The significant variation in ductility – consistent with the limited number of grain boundaries being present – is rationalised using a crystal plasticity approach calibrated by experiments on single crystals loaded along the <001>, <011>, and <111> directions. Quantitative strength and toughness values for the grain boundaries are estimated using a cohesive zone method. The modelling approach is used to determine an approximation of the size of the representative volume element (RVE) needed for volume-averaged behaviour.